A COMPARATIVE STUDY OF ACADEMIC ADVISING SYSTEM IN FOUNDATION PROGRAMS AND THE DEVELOPMENT OF A WEB-BASED ADVISING INTERFACE FOR MALAYSIAN UNIVERSITIES (Proceedings of the International Conference on Education, 2025)
Academic advising plays a vital role in supporting student success, especially in foundation programs where clear and structured guidance helps students transition smoothly into higher education. In Malaysia, traditional advising methods face challenges such as limited accessibility, inefficient communication, and a lack of real-time monitoring. These obstacles can make it difficult for advisors to provide timely, personalized support to students who may need extra help. This study compares academic advising practices in Malaysia with those in the United States, United Kingdom, and Australia to identify key gaps and areas for improvement. The findings reveal several critical issues, including unstructured advising frameworks, limited advisor training, and low adoption of digital tools. To address these challenges, a web-based academic advising system was developed specifically for foundation students. This system enhances communication, enables real-time tracking of academic progress, and supports early intervention efforts to assist students who may be at risk. Key features include personalized dashboards for both students and advisors, structured advising checklists, and a centralized platform designed to efficiently manage student inquiries. The system’s interface and functions were carefully designed to align with international best practices while effectively addressing common advising problems found in local institutions. By integrating these elements, the proposed system offers a practical and flexible solution to improve advising services. Ultimately, it aims to boost student engagement, facilitate timely academic decisions, and contribute to better overall academic outcomes for foundation students.
Keywords: academic advising; foundation programs; web-based system; advising system development; Academic Advising, Foundation Programs, Web-Based System, Advising System Development, Malaysia, Student Tracking; student tracking